Radio- and Power-Over-Fiber Integration for 6G Networks: Challenges and Future Prospects - Leticia Carneiro de Souza; Victoria Dala Pegorara Souto; Arismar Cerqueira Sodre (IEEE Access)
The rapid evolution of wireless communication networks has fueled the demand for high-speed data transmission and low-latency connectivity. As the world looks toward the development of sixth-generation (6G) Networks, the need for innovative power distribution solutions becomes critical. Power-over-fiber (PoF) technology has emerged as a promising candidate for addressing these challenges by enabling the delivery of power through optical fibers. This review paper focuses on the future prospects of PoF technology for 6G Networks, with a particular emphasis on the integration of the radio-over-fiber (RoF) technique. In this context, we explore the application scenarios for radio- and power-over-fiber (RPoF) systems, enabling simultaneous data and power transmission over optical fibers. Furthermore, we discuss the underlying principles of PoF systems, including operation and key components, e.g., high-power laser diode (HPLD), optical fiber, and photovoltaic power converter (PPC), highlighting their key features, performance metrics, and design considerations. A comprehensive analysis of the current state of PoF technology is also presented, focusing on its potential applications in the context of 6G Networks. Furthermore, the main challenges and limitations of RPoF systems are identified, including power transmission efficiency (PTE), optical fiber design and deployment, scalability, capacity, safety, and reliability. Finally, we discuss the potential research directions and technological advancements needed to fully exploit the capabilities of RPoF in the 6G era.